Synthetic Cathinones Induce Developmental Arrest, Reduce Reproductive Capacity, and Shorten Lifespan in the C. elegans Model - Cristina Mendes; Daniela Maia; Ricardo Jorge Dinis-Oliveira; Fernando Remião; Renata Silva; Daniel José Barbosa (Journal of Xenobiotics)
Drug abuse presents a significant global health challenge as the illicit drug market progresses from classic drugs to a growing prevalence of New Psychoactive Substances (NPS), particularly synthetic cathinones, which, although illegal, are often falsely marketed as safe and legal alternatives. The rapid increase in the use of these drugs complicates the assessment of their safety and effects on human health. However, they pose unique toxicological concerns that remain largely uncharacterized. This study investigated the toxic effects of three synthetic cathinones, namely, methylone, pentedrone, and 4-methylethcathinone (4-MEC), using the model organism C. elegans. We assessed the impact of these substances on animal survival, development, reproductive behavior, and longevity. Our results showed that short-term exposure (24 h) to concentrations of 5.0 mM or higher significantly reduced animal survival rates, while prolonged exposure (72 h) led to more pronounced toxicity, significantly reducing survival rates at concentrations as low as 1.0 mM. Moreover, sublethal concentrations resulted in developmental arrest. Additionally, pentedrone impaired reproductive capacity, while 4-MEC significantly shortened C. elegans lifespan. These findings highlight the urgent need for further investigation into the implications of synthetic cathinone use on human health through in vivo models as their prevalence in the illicit drug market continues to rise.